Hematological Profile of Malnadgidda Breed of Cattle in Karnataka - Sripad, K.; Hegde, Ganesh; Giridhar, P.; Byregowda, S.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
In the present study a total 107 apparently healthy Malnadgidda animals belonging to individual farmers across eleven talukas of Uttara Kannada district were included. Animals were grouped into male and female, 0-3, 3-6, 6-9 and 9-12 years of age and based on the geographic regions into upper Ghat and lower Ghat/Coastal region of Uttara Kannada district. Blood samples with anticoagulants were collected from these animals and haematological parameters TEC, TLC, Hb, PCV, MCV, MCH, MCHC and PLT were determined. The average value of 7.55±0.18x106, 12.72±0.41x103, 8.05±0.17, 31.91±0.69, 45.97±3.00, 10.66±1.17, 26.79±1.91and 221.8±10.12x103 were observed for TEC, TLC, Hb, PCV, MCV, MCH,MCHC and PLT respectively. Significantly higher TLC values was observed in the Malnadgidda as compared to Deoni and but did not differ significantly with Khillar and Krishnavalley breed. The established haematological values in present study could be used as reference values in Malandgidda breed .
Keywords: Haematology Malnadgidda breed; Karnataka